Menstrual health intervention and school attendance in Uganda (MENISCUS-2): a pilot intervention study. Issue 2 (4th February 2020) - Kansiime, Catherine; Hytti, Laura; Nalugya, Ruth; Nakuya, Kevin; Namirembe, Prossy; Nakalema, Shamirah; Neema, Stella; Tanton, Clare; Alezuyo, Connie; Namuli Musoke, Saidat; Torondel, Belen; Francis, Suzanna C; et al.
Abstract : Objectives: Achieving good menstrual health and hygiene (MHH) is a public health challenge and there is little evidence to inform interventions. The aim of this study was to pilot test an intervention to improve MHH and school attendance in Uganda, in preparation for a future cluster-randomised trial. Design: Longitudinal study with pre–post evaluation of a pilot intervention. Setting: Two secondary schools in Entebbe, Uganda. Participants: Of the 473 eligible students in secondary 2 (S2) at baseline, 450 (95.1%; 232 girls and 218 boys) consented/assented. 369 students (188 girls; 81.0%; and 181 boys; 83.0%) participated in the endline survey. Intervention: The intervention comprised training teachers to improve delivery of government guidelines for puberty education, training in use of a menstrual kit and pain management, a drama skit, provision of analgesics and improvements to school water and sanitation hygiene facilities. Primary and secondary outcome measures: Feasibility and acceptability of delivering the intervention. Baseline and endline quantitative surveys were conducted, with qualitative interviews conducted at endline. School attendance was assessed using self-completed daily diaries among a nested cohort of 100 female students. Results: There were high levels of uptake of the individual and behavioural intervention components (puberty education, drama skit, menstrual hygiene management (MHM) kit and pain management). The proportion of girls reporting anxiety about next period decreased from 58.6% to 34.4%, and reported use of effective pain management increased from 76.4% to 91.4%. Most girls (81.4%) reported improved school toilet facilities, which improved their comfort managing menstruation. The diary data and qualitative data indicated a potential intervention impact on improving menstrual-related school absenteeism. Conclusions: The pilot study showed that the multicomponent MHM intervention was acceptable and feasible to deliver, and potentially effective in improving menstruation knowledge and management. A cluster-randomised trial is needed to evaluate rigorously the intervention effects on MHM and school attendance. Trial registration number: NCT04064736 ; Pre-results.